The Effect of The Learning Cell Model on Students' Mathematical Communication Skills - Aisyah Inayatullah Atnar; Rini Asnawati; Mella Triana (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to determine the effect of The Learning Cell model on students' mathematical communication skills. The population in this study consists of all eighth-grade students of SMP Negeri 16 Bandar Lampung in the 2024/2025 academic year totaling 264 students distributed across nine classes. The sample in this study includes class VIII E as the experimental class with 30 students and class VIII G as the control class with 29 students selected using purposive sampling technique. The type of research used is quasi experimental research. The design used is the pretest-posttest control group design. The data in this study is quantitative data obtained through a mathematical communication skills test. Based on the result of hypothesis test using t-test, it was found that the average gain score of mathematical communication skills for students who participated in The Learning Cell model was 0.72, which was higher than the average gain score of 0.58 achieved by students who participated in conventional learning. It can be concluded that the implementation of The Learning Cell model has an effect on students' mathematical communication skills.